Pengaruh Pemberian Uap Etanol dan Suhu Penyimpanan Terhadap Mutu dan Masa Simpan Brokoli (Brassica oleracea L.) - Iriandi Perdana Putra; I Made Supartha Utama; I A Rina Pratiwi Pudja (Jurnal BETA (Biosistem dan Teknik Pertanian), 2014)
This research aimed to determine the effect of ethanol vapor and storage temperature on quality and shelf life of broccolies. The research used completely randomized design (CRD) with two factors of treatments. The first factor was ethanol vapor treatment with 4 levels of consentrations; 0%, 10%, 20% and 30%. The second factor was the storage temperature, consisting of 2 levels; room temperature (26?) and low temperature 2?. The florets of broccoli as controls were prepared without treatment of ethanol vapor and placed at room temperature and low temperature. The measured parameters were: respiration rate, hardness, color and sensory evaluation includes flavor, color, smell, freshness, and crispness. The data were satistically analysed using analysis of variance. The significant result of the analysis was folowed by the test of Least Significant Difference (LSD 5%). The results showed that ethanol vapor concentration 10% was the best treatment since it could effectively maintain the level of greenness of broccoli by up to the day 5 with a value of -6,23 compared to controls. Ethanol vapor treatment and storage temperatur had no significant effect on the hardness level of the florets on stalk of broccoli. The rate of respiration was affected by storages temperature. At the room temperature, the comsumption of O2 increased until day 5 about 102,2 to 193,17 ml O2/kg.hr while at low temperature, the O2 consumption was lower until day 15 were approximately 65,4 to 60,4 ml O2/kg.hour. Sensory evaluation showed that the broccoli was maintain quality by up to day 4 at room temperature, while in cold storage can extended the shelf life by up to 8 day.